Schottky-barrier quantum well in two-dimensional semiconductor nanotransistors. (December 2020) - Jiang, Jinbao; Doan, Manh-Ha; Sun, Linfeng; Ghimire, Mohan Kumar; Kim, Hyun; Yun, Seok Joon; Yang, Heejun; Duong, Dinh Loc; Lee, Young Hee
Abstract: Two-dimensional (2D) semiconductors are promising candidates for quantum-well devices with the inherent quantum confinement of the subnanometer thickness along the out-of-plane direction. Coulomb/quantum oscillation phenomena have been demonstrated in 2D semiconductors devices, including artificial quantum dots with local electrostatic gating and stacked heterostructure quantum wells. However, the exact quantized energy states, let alone the complexity of the device structures and low observation temperature, have not been clearly revealed. Here, we report a rational fabrication platform of 2D semiconductor nanotransistors to directly construct a Schottky-barrier quantum well (SB-QW) for quantized energy states engineering. The feature size of the quantum well is tailored by a vertical nanochannel of monolayer transition metal dichalcogenides (TMDCs) via an insulating spacer. Meanwhile, the potential barrier is constructed by the Schottky barrier. Quantum oscillations are clearly observed and the quantized energy states are extracted from the source-drain current modulated with the gate bias. Such quantum oscillations are preserved up to ~100 K with a channel length of approximately 16 nm. With an evaluated Schottky barrier height of approximately 27 meV, the quantized energy states are estimated from 2 to 24 meV near the conduction band edge, consistent with corresponding explicit principal quantum numbers. Our work demonstrates the feasibility of moving 2D van der Waals semiconductor nanotransistors towards quantum transistors. Graphical abstract: Image 1 Highlights: A Schottky-barrier quantum well in 2D nanotransistors is proposed as a universal platform for modulating quantized states. The quantum well width of MoS2 approaches ~16 nm, giving rise to the observation of quantum oscillations up to ~100K. The estimated quantized energy levels match well with the textbook model of a finite potential quantum well.